Analisis Efektivitas Pemungutan Pajak Bumi Dan Bangunan Pedesaan Dan Perkotaan Tahun 2018-2022 Di Kecamatan Sukatani Kabupaten Bekasi - Dahuri, Adin; Yani, Ahmad (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
The collection realization of land and property tax of rural and urban area in Sukatani District of Bekasi Regency within 2018-2022 reached 43,01% until 57,30% of determined target. Such achievements concluded that the realization revenues were not effective. The achievement also showed that efforts regarding the collection were not optimal. Instead of such less efforts, the failure of target achievement aslo influenced by some obstacles in tax collection, such as unsufficient employees and lack of taxpayer awareness. Sukatani's authority establishes special task force to increase tax collection in the following years. The task force must implement three specific duties: collect tax by manual payment intensively, coordinate with land ownership certification body and promotes the utilization of online payment by using Sapa Bekasi Application